Back Cover: Semiconducting and Plasmonic Copper Phosphide Platelets (Angew. Chem. Int. Ed. 26/2013). Issue 26 (10th June 2013) - Manna, Goutam; Bose, Riya; Pradhan, Narayan
<x xml:space="preserve">Abstract</x> Size‐tunable Cu3P platelets can be synthesized in the nano‐ to micrometer‐size range by controlling the nucleation density, as described by N. Pradhan et al. in their Communication on page 6762 ff. These platelets show high‐contrast Moiré patterns, absorb light over most of the solar spectrum, and show localized surface plasmon resonance in the NIR region. These properties, along with a high extinction coefficient and their rectification behavior, make them potential photovoltaic materials.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>